Polymer-Surfactants Physiochemical Interaction for Enhancing the Flow and Mechanical Characteristics of Polymeric Drag Reducing Agent - Oluwasoga, Akindoyo Edward; Abdulbari, Hayder A. (2014)
Frictional pressure in turbulent flows attributed to pipes and eddies interaction are great challenges that increase coast of transporting liquids in pipelines since high rate of energy is consumed, often prevented in many ways such as polymeric additives introduced in low concentrations, but degrade over critical shear stress for their high molecular weight and long chain, surfactants are introduced to form complexes with the polymer to generating threadlike self repairing micelles if cationic surfactants with organic salts, could yield greater drag reduction since the ions are capable of entangling strongly to the micellar structures formed at low concentration (1mM). In this present work, catonic benzalkonium chloride surfactant, its sodium salicylate counterion with droplets of alcohol was mixed with non ionic polyacrylamide polymer, varied concentrations of surfactants, polymers and their complex mixtures were prepared, to investigate their physiochemical behaviors and drag reduction in Brookfield Viscometer and rotating disk apparatus at 3000 maximum rpm respectively. 47% drag reduction was observed where complex mixtures gave better performance than individual materials. Although the micellar aggregates formed degraded after a period of time which was partly repaired but longer drag reduction was observed confirming the critical role by the complex mixtures.